Theory of traditional Chinese medicine and therapeutic method of diseases - Lu, Ai-Ping (World J Gastroenterol, 2004)
Traditional Chinese medicine, including herbal medicine and acupuncture, as one of the most important parts in complementary and alternative medicine (CAM), plays the key role in the formation of integrative medicine. Why do not the modern drugs targeting the specificity of diseases produce theoretical effects in clinical observation? Why does not the traditional Chinese medicine targeting the Zheng (syndrome) produce theoretical effects in clinic? There should have some reasons to combine Western medicine with Chinese herbal medicine so as to form the integrative medicine. During the integration, how to clarify the impact of CAM theory on Western medicine has become an emergent topic. This paper focuses on the exploration of the impact of theory of traditional Chinese medicine on the therapy of diseases in Western medicine.